Searching for archaic contribution in Africa. (17th February 2019) - Santander, Cindy; Montinaro, Francesco; Capelli, Cristian
Abstract: Context: Africa's role in the narrative of human evolution is indisputably emphasised in the emergence of Homo sapiens . However, once humans dispersed beyond Africa, the history of those who stayed remains vastly under-studied, lacking the proper attention the birthplace of both modern and archaic humans deserves. The sequencing of Neanderthal and Denisovan genomes has elucidated evidence of admixture between archaic and modern humans outside of Africa, but has not aided efforts in answering whether archaic admixture happened within Africa. Objectives: This article reviews the state of research for archaic introgression in African populations and discusses recent insights into this topic. Methods: Gathering published sources and recently released preprints, this review reports on the different methods developed for detecting archaic introgression. Particularly it discusses how relevant these are when implemented on African populations and what findings these studies have shown so far. Results: Methods for detecting archaic introgression have been predominantly developed and implemented on non-African populations. Recent preprints present new methods considering African populations. While a number of studies using these methods suggest archaic introgression in Africa, without an African archaic genome to validate these results, such findings remain as putative archaic introgression. Conclusion: In light of the caveats with implementing current archaic introgression detection methods in Africa, we recommend future studies to concentrate on unravelling the complicated demographic history of Africa through means of ancient DNA where possible and through more focused efforts to sequence modern DNA from more representative populations across the African continent.